Challenging the Claim of Ijma' on the Prohibition of Bank Interest: A Critical Review of Murabahah Practices in Islamic Banking - Yanti, Hani Esa; Aziz, Jamal Abdul (IAIN Manado, 2025)
The global Islamic finance industry is growing rapidly, with its primary legitimacy resting on the claim of ijmāʿ (scholarly consensus) regarding the prohibition of bank interest. However, murabahah contracts, which dominate 76.95% of Indonesian Islamic banking financing, have received structural criticism similar to that of the interest system. This study analyzes the validity of the ijmāʿ claim regarding the prohibition of bank interest, according to uṣūl al-fiqh (principles of Islamic jurisprudence), and examines whether murabahah practices contain elements that lead to the interest system. Qualitative research with descriptive-analytical and critical-evaluative library research approach using data from classical uṣūl al-fiqh texts (Khallaf, al-Shāfiʿī) and 33 journal articles (2000-2025). Analysis was conducted through data reduction, comparative analysis, critical-methodological evaluation, and source triangulation. The ijmāʿ claim regarding the prohibition of bank interest does not meet the requirement of an agreement among all mujtahids (qualified scholars capable of independent reasoning) without exception, due to ongoing disagreements and methodological debates; thus, it is more appropriately categorized as a jumhūr (majority) opinion. Murabahah practices contain three elements leading to the interest system: the bank's role as a disguised financier with risk transfer to customers, mark-up systems influenced by market interest rates and varying based on time period (implicit recognition of time value of money), and structural-functional similarity with interest-bearing financing confirmed by empirical studies (12.87% margin approaching conventional rates). The double inconsistency between methodologically invalid ijmāʿ claims and murabahah practices resembling interest creates risks of a credibility crisis. Reconstruction is necessary through genuine ownership, a real economy-based margin setting, transparency, reorientation towards PLS (Profit and Loss Sharing), and strengthened shari'ah supervision.